(untitled) (Revista Brasileira de Plantas Medicinais, 2020)
Mentha x villosa, commonly known in Brazil as hortelã miuda (small mint), is a medicinal plant widely used to treat gastrointestinal disorders. Vegetal tissue culture enables the in vitro multiplication and conservation of many species that are or might become commercially important. Thus this research aims to develop an in vitro multiplication and conservation protocol of Mentha x villosa in order to supply health managers and pharmacies belonging to the Farmácia Viva project with seedlings. To achieve our objective nodal segments of plants growing in the fields were disinfected and transferred to Petri dishes containing MS culture medium supplemented with 30 g/l sucrose, and kept under controlled conditions. After 21 days the responsive explants were transferred to Petri dishes containing the same culture medium supplemented with 1.0 mg/l BAP. On the 45th day the explants were transferred to flasks with MS medium supplemented with sucrose and BAP in the concentrations of 0.0; 0.5; 1.0; and 1.5 mg/l. A completely randomized factorial experiment with 6 repetitions consisting of 6 flasks with 3 nodal segments each was designed. After 60 days the percentage of responsive explants (explants with shoot development) and the number of shoots per explant were evaluated. Plants were acclimatized for 30 days before survival assessment. Some micropropagated plants were used for in vitro conservation experiments during which nodal segments of approximately 1.5 cm were inoculated in different concentrations of MS medium (MS, MS/2 e MS/4) and sucrose (15 e 30 g/l). The flasks were kept in an acclimatization BOD chamber at 20 ºC. On the thirtieth culture day the following variables were evaluated: height, number of senescent leaves, and number of branches and roots. After 120 days plant feasibility in different treatments was determined using the same variables mentioned above. The addition of BAP to the culture medium increased the in vitro multiplication of mint shoots, maximum proliferation being obtained in the concentration of 1,5 mg/l. Hundred percent survival was observed during acclimatization. Our results show that in vitro conservation of mint plants without cultivars during 120 days is a feasible process when using MS medium a quarter of its concentration with addition of 30 g/l sucrose.